Determinants of the Portuguese government bond yields - Pinho, A.; Barradas, R. (International Journal of Finance and Economics, 2021)
This paper conducts an empirical examination of the determinants of the 10‐, 5‐ and 1‐year Portuguese government bond yields by performing a time series econometric analysis for the period between the first quarter of 2000 and the last quarter of 2016. The literature suggests that the evolution of government bond yields depends on three main risk drivers, namely credit risk, global risk aversion and liquidity risk. We estimate three equations for the 10‐, 5‐ and 1‐year Portuguese government bond yields, including eight independent variables (macroeconomic performance, fiscal conditions, foreign borrowing, the inflation rate, labour productivity, the demographic situation, global risk aversion and liquidity risk) to take into account all three risk drivers referred to in the literature. Our results show that there are no significant differences in the determinants of the Portuguese government bond yields among the different maturities, either in the long term or in the short term. Our results also confirm that all three of the risk drivers have exerted a strong influence on the evolution of the Portuguese government bond yields. Liquidity risk, foreign borrowing and the inflation rate are the main triggers of the rise in the Portuguese government bond yields, which does not counterweigh the beneficial effects played by the fiscal conditions, labour productivity and demographic situation.